The girl and the bicycle - Pett, Mark (New York, New York : Simon & Schuster Books for Young Readers, 2014)
A wordless picture book in which a girl sees a bicycle she wants to buy, works hard for a kindly neighbor to earn the money for it, then gets a pleasant surprise.
"A Junior Library Guild selection"--Jkt. flap.
All ages.
Keywords: Moneymaking projects -- Fiction; Friendship -- Fiction; Bicycles and bicycling -- Fiction; Stories without words; Money-making projects for children -- Juvenile fiction; Friendship -- Juvenile fiction; Bicycles -- Juvenile fiction; Stories without words; Bicycles; Friendship; Money-making projects for children; Stories without words; Fiction; Juvenile works